Perancangan Ulang Interior Madrasah Aliyah Assakinah Di Kota Cimahi Dengan Pendekatan Psikologi Ruang - Rizky Wiguna, Gani; Haryotedjo, Tri; Sudarisman, Irwan (eProceedings of Art & Design, 2024)
This study examines the evolution of the concept of school from informal activities during children's leisure time to a formal institution for teaching and learning. The primary focus is on Madrasah Aliyah (MA) Assakinah, established in 2012, which aims to meet the standards of the Merdeka curriculum. The research identifies challenges in creating an optimal learning environment, particularly concerning existing furniture. Physical discomfort, such as non-ergonomic furniture, inadequate lighting, and unhelpful room layout, may affect students' psychology and learning effectiveness. This study emphasizes the importance of redesigning the interior with a spatial psychology approach to enhance student comfort. Improvements in design elements such as furniture, layout, and lighting are expected to create a more harmonious learning environment that supports the Merdeka curriculum and enhances students' academic performance. Keywords: furniture, madrasah aliyah, psychology